PERAN PERILAKU KEUANGAN DAN INKLUSI KEUANGAN DALAM MENJAGA KEBERLANGSUNGAN USAHA UMKM DI KOTA BATU: Financial Behavior, Financial Inclusion and Business Continuity - Mukoffi, Ahmad; Himawan Wibisono, Sukarno; As’ adi, As’ adi; Sularsih, Hermi (Jurnal Paradigma Ekonomika, 2025)
Business sustainability refers to the ability of enterprises to maintain continuous operations through sound management practices, including business development, expansion, and adaptive decision-making in response to a dynamic business environment. In the context of micro, small, and medium enterprises (MSMEs), sustainability is largely influenced by internal factors, particularly the financial behavior of business owners and their level of financial inclusion. This study aims to examine the role of financial behavior and financial inclusion in sustaining MSMEs in Batu City.This research adopts a quantitative approach with a causal-associative research design. Data were collected through a survey using structured questionnaires distributed to MSME owners in Batu City. The collected data were analyzed using hypothesis testing techniques to assess both partial and simultaneous effects of financial behavior and financial inclusion on business sustainability.The findings indicate that financial behavior and financial inclusion play a significant role in supporting the sustainability of MSMEs in Batu City. Individually, both variables contribute positively to the ability of MSME owners to maintain and develop their businesses. Simultaneously, financial behavior and financial inclusion demonstrate a strong combined influence on MSME sustainability. These results highlight the importance of strengthening financial management capabilities and expanding access to inclusive financial services as strategic efforts to enhance the long-term sustainability of MSMEs.